Fuel cell PV fed hybrid energy sources for 3 phase matrix converter using 3D Space Vector Modulation - Palanisamy, R.; Thentral, T. M.Thamizh; Usha, S.; Geetha, A.; Saleel, C. Ahamed; Rajendran, Parvathy; Lee, It Ee; Hussain, Fayaz (Nature Research, 2026)
The increasing global demand for clean and sustainable energy has driven the integration of renewable energy sources with advanced power electronic converters. This paper presents a novel hybrid energy system combining Proton Exchange Membrane Fuel Cell (PEMFC) and Photovoltaic (PV) sources to feed a three-phase matrix converter (MC), employing a 3D Space Vector Modulation (3D-SVM) strategy. The hybrid configuration ensures a stable and continuous power supply, overcoming the intermittency of solar energy and the slow dynamic response of fuel cells. The 3-phase matrix converter, recognized for its bidirectional power flow, compact structure, and high-quality output, is controlled using the 3D-SVM technique to achieve improved voltage transfer ratio, minimized Total Harmonic Distortion (THD), reduced Common Mode Voltage (CMV), less neutral current, and enhanced dynamic performance. The proposed modulation strategy optimally synthesizes switching state vectors in 3D-cubic region, ensuring effective real-time control and power management of the hybrid energy system. The simulation and hardware results of the proposed system validates the performance of 3-phase matrix converter with hybrid energy sources.